Investigations into the Sarcomeric Protein and Ca2+-Regulation Abnormalities Underlying Hypertrophic Cardiomyopathy in Cats (Felix catus) - Messer, Andrew E.; Chan, Jasmine; Daley, Alex; Copeland, O'Neal; Marston, Steven B.; Connolly, David J. (Frontiers in Physiology, 2017)
Hypertrophic cardiomyopathy (HCM) is the most common single gene inherited cardiomyopathy. In cats (felix catus) HCM is even more prevalent and affects 16% of the outbred population and up to 26% in pedigree breeds such as Maine Coon and Ragdoll. Homozygous MYBPC3 mutations have been identified in these breeds but the mutations in other cats are unknown. At the clinical and physiological level feline HCM is closely analogous to human HCM but little is known about the primary causative mechanism. Most identified HCM causing mutations are in the genes coding for proteins of the sarcomere. We therefore investigated contractile and regulatory proteins in left ventricular tissue from 275 cats, 18 diagnosed with HCM, including a Ragdoll cat with a homozygous MYBPC3 R820W, and 78 non-HCM cats in comparison with human HCM (from septal myectomy) and donor heart tissue. Myofibrillar protein expression was normal except that we observed 20-44% MyBP-C haploinsufficiency in 5 of the HCM cats. Troponin extracted from 8 HCM and 5 non-HCM cat hearts was incorporated into thin filaments and studied by in vitro motility assay. All HCM cat hearts had a higher (2.06±0.13 fold) Ca2+-sensitivity than non-HCM cats and, in all the HCM cats, Ca2+-sensitivity was not modulated by troponin I phosphorylation. We were able to restore modulation of Ca2+-sensitivity by replacing troponin T with wild-type protein or by adding 100µM Epigallocatechin 3-gallate (EGCG). These fundamental regulatory characteristics closely mimic those seen in human myectomyHCM samples HCM indicating a common molecular mechanism that is independent of the causative mutation. Thus the HCM cat is a potentially useful large animal model.